2004
DOI: 10.4319/lo.2004.49.4.1123
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of coastal planktonic diatoms from benthic versus pelagic cells: Variations in bloom development and species composition

Abstract: Although phytoplankton blooms are major events in aquatic systems, the importance of benthic resting stages in seeding planktonic blooms is still unclear. Using microcosms, we tested the influence of benthic versus planktonic inocula on the development and taxonomic composition of diatom communities in a temperate fjord. Experiments in early spring 2002, fall 2002, and late spring 2003 showed that the type and quantity of inoculum influenced bloom development and composition. Species composition was vastly dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 37 publications
2
42
0
1
Order By: Relevance
“…Hence, the relatively low number of resting stages recorded in this study might be explained either by the low frequency of sexual events that precede the formation of spores in L. da nicus and/or the numerical dominance of Leptocylindrus species or varieties that do not form resting spores at all. This might also be the reason why L. danicus, while relatively abundant in the plankton, did not show high abundances of resting stages in the sediments collected in a Swedish fjord, and was mostly recorded in microcosms inoculated with phytoplankton samples (McQuoid & Godhe 2004). A considerable fraction of the diatoms that germinated from surface sediments of the Gulf of Naples was constituted by small-sized Thalassiosira-like cells.…”
Section: Diversity Of Resting Stagesmentioning
confidence: 98%
See 1 more Smart Citation
“…Hence, the relatively low number of resting stages recorded in this study might be explained either by the low frequency of sexual events that precede the formation of spores in L. da nicus and/or the numerical dominance of Leptocylindrus species or varieties that do not form resting spores at all. This might also be the reason why L. danicus, while relatively abundant in the plankton, did not show high abundances of resting stages in the sediments collected in a Swedish fjord, and was mostly recorded in microcosms inoculated with phytoplankton samples (McQuoid & Godhe 2004). A considerable fraction of the diatoms that germinated from surface sediments of the Gulf of Naples was constituted by small-sized Thalassiosira-like cells.…”
Section: Diversity Of Resting Stagesmentioning
confidence: 98%
“…Garrison 1981, Pitcher 1990, Itakura et al 1997, McQuoid & Godhe 2004. As for resting cells, which cannot be distinguished from vegetative cells, information on their presence, abundance and fate in the natural environment is rather elusive (Anderson 1975, but see Härnström et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown for complex diatom communities that single species recruitment strategies and conditions prevailing during the seeding stage may significantly affect later community structure and dominance distribution (McQuoid & Godhe 2004). Efficient recruitment from the large benthic seed populations (Kremp 2000, Kremp & Anderson 2000 together with coinciding selective hydrographical conditions obviously are important prerequisites for later dinoflagellate prevalence in the spring phytoplankton community.…”
Section: Role and Sources Of Initial Dinoflagellate Abundance For Blomentioning
confidence: 99%
“…Particularly in multispecies communities, such as the phytoplankton spring bloom in the Baltic Sea, successful prevalence in the competition for resources may entirely depend on initial conditions (Huisman & Weissing 2001). Besides hydrochemical and hydrographic conditions, those may include presence and relative abundance of competitors and grazers, as well as specific recruitment strategies (Anderson et al 2002, McQuoid & Godhe 2004. 'Being in the right place at the right time' may be a more important prerequisite for successful prevalence of a species in a community than favourable habitat conditions or ecophysiological adaptations (Smayda & Reynolds 2001, Anderson et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its high abundance, it is important to understand the ecology of Chaetoceros in natural waters from the viewpoint of primary production. In the genus, Chaetoceros tenuissimus Meunier is well-known as a cosmopolitan species (Meunier 1913, Hasle & Syvertsen 1996, Sunesen et al 2008, McQuoid & Godhe 2004) and our preliminary study shows that the species causes blooms in the coastal waters in Japan (unpubl.). Shirai et al (2008) reported the existence of a virus infecting C. tenuissimus, however, the host-virus relationships in natural environments are only poorly understood due to the lack of data on the host dynamics.…”
Section: Introductionmentioning
confidence: 99%